Economic Distress, Community Context, and Intimate Violence in the United States, 1988 and 1994 - Benson, Michael L. ([Verlag nicht ermittelbar], 2002)
Because of their restricted access to financial resources, couples undergoing economic distress are more likely to live in disadvantaged neighborhoods than are financially well-off couples. The link between individual economic distress and community-level economic disadvantage raises the possibility that these two conditions may combine or interact in important ways to influence the risk of intimate violence against women. This study examined whether the effect of economic distress on intimate violence was stronger in disadvantaged or advantaged neighborhoods or was unaffected by neighborhood conditions. This project was a secondary analysis of data drawn from Waves 1 and 2 of the National Survey of Families and Households (NSFH) and from the 1990 United States Census. From the NSFH, the researchers abstracted data on conflict and violence among couples, as well as data on their economic resources and well-being, the composition of the household in which the couple lived, and a large number of socio-demographic characteristics of the sample respondents. From the 1990 Census, the researchers abstracted tract-level data on the characteristics of the census tracts in which the NSFH respondents lived. Demographic information contains each respondent's race, sex, age, education, income, relationship status at Wave 1, marital status at Wave 1, cohabitation status, and number of children under 18. Using variables abstracted from both Wave 1 and Wave 2 of the NSFH and the 1990 Census, the researchers constructed new variables, including degree of financial worry and satisfaction for males and females, number of job strains, number of debts, changes in debts between Wave 1 and Wave 2, changes in income between Wave 1 and Wave 2, if there were drinking and drug problems in the household, if the female was injured, number of times the female was victimized, the seriousness of the violence, if the respondent at Wave 2 was still at the Wave 1 address, and levels of community disadvantage.